Organic-inorganic composite ultraviolet absorbent, anti-ultraviolet aging polyethylene plate as well as preparation method and application of organic-inorganic composite ultraviolet absorbent and anti-ultraviolet aging polyethylene plate
By using organic-inorganic composite ultraviolet absorbers in the polyethylene height-regulating pad, the problem of aging of polyethylene plates under ultraviolet light erosion is solved, and the resistance to UV aging and mechanical properties are significantly improved, which is suitable for extreme environments.
Patent Information
- Application Number
- CN202411727057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing polyethylene-adjustable pads age under ultraviolet erosion, resulting in unsafe use status and service life, especially in extreme environments.
The organic-inorganic composite ultraviolet absorber, including benzophenone hydrochloride and rare earth cerate, is prepared by sol-gel method, and the stability and compatibility of benzophenone compounds are improved by chemical modification of organic amine hydrochloride, forming a synergistic organic-inorganic composite ultraviolet absorber, and added to polyethylene resin to improve the resistance to UV aging.
It significantly improves the anti-UV aging performance of polyethylene plates, so that they can be used in long-term ultraviolet radiation environment without degradation in performance, extends service life, and improves mechanical properties, and is suitable for extreme environments such as high altitude and strong ultraviolet rays.
Smart Images

Figure CN119552422A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an organic-inorganic composite ultraviolet absorber, an anti-ultraviolet aging polyethylene plate, and a preparation method and application thereof. Background Art
[0002] In recent years, my country's railway development has been rapid. As the design speed of trains increases, higher requirements are placed on the stability and safety of train operation. In order to make the train more stable during driving, heightening pads are generally set under the rails to achieve shock absorption. Since the rail operation conditions are relatively harsh, with heavy loads, outdoor use and long service life, the pads are required to have excellent performance.
[0003] Existing height adjustment pads are often made of steel plates, rubber, nylon or polyethylene composite materials. Polyethylene, as an engineering plastic, has excellent physical properties, chemical stability and light mass density, and has certain properties such as wear resistance, impact resistance and corrosion resistance, making it an ideal material for manufacturing height adjustment pads. However, polyethylene height adjustment pads are extremely susceptible to erosion and aging by ultraviolet light, which poses certain hidden dangers to the safe operation of railways. Especially in some harsh environmental areas, such as extreme environments with high altitudes, high ultraviolet rays, and extremely low temperatures, the use status and service life of polyethylene height adjustment pads cannot be guaranteed. Therefore, it is urgent to develop a polyethylene height adjustment pad for high-speed railways that is resistant to ultraviolet aging. Summary of the invention
[0004] Aiming at the problem that the existing polyethylene composite materials in the prior art have poor anti-ultraviolet aging performance and cannot meet the requirements in terms of usage status and service life when applied to high-speed railways, the present invention provides an organic-inorganic composite ultraviolet absorber, an anti-ultraviolet aging polyethylene plate, and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] In the first aspect, the present invention provides an organic-inorganic composite ultraviolet absorber, comprising a benzophenone hydrochloride and a rare earth cerate A2Ce2O7 as shown in formula (I);
[0007]
[0008] Among them, R1 and R2 are H or CH3, R3 is a C2-C3 alkyl group, R4 is a C1-C8 alkyl group, R5 is H or a sulfonic acid group; and A represents La, Gd or Y.
[0009] Compared with the prior art, in the organic-inorganic composite ultraviolet absorber provided by the present invention, benzophenone hydrochloride has extremely strong ultraviolet absorption performance, and has good compatibility with organic resins, and can be applied to a variety of organic resin matrices to enhance the ultraviolet aging resistance of organic resins; at the same time, the inorganic ultraviolet absorber rare earth cerate A2Ce2O7 has a smaller bandgap width, can absorb shorter wavelength light, and cooperates with benzophenone hydrochloride to make the material have a wider spectrum absorption capacity in the ultraviolet region. The above-mentioned organic-inorganic composite ultraviolet absorber can be applied to a variety of organic resin systems, so that the material can be used in a long-term ultraviolet radiation environment without performance degradation, meet the needs of various application scenarios, and have broad application prospects.
[0010] In a second aspect, the present invention provides a method for preparing an organic-inorganic composite ultraviolet absorber, comprising the following steps:
[0011] Step a, adding a benzophenone compound represented by formula (II), an organic amine hydrochloride represented by formula (III) and an acid binding agent into an organic solvent, heating to reflux, and keeping the temperature to react to obtain a benzophenone hydrochloride represented by formula (I);
[0012]
[0013] Step b, dissolving rare earth nitrate and cerium nitrate in water to obtain a mixed salt solution; adding a complexing agent and a stabilizer to the mixed salt solution, mixing evenly, adjusting the pH to 6-7, heating at 90° C.-100° C. to a gel state, drying, grinding, and calcining to obtain rare earth cerate;
[0014] Step c, adding the rare earth cerate and the silane coupling agent into water, mixing evenly, to obtain a rare earth cerate dispersion; adding the benzophenone hydrochloride into the rare earth cerate dispersion, stirring for reaction, solid-liquid separation, and drying to obtain an organic-inorganic composite ultraviolet absorber.
[0015] The invention provides a method for preparing an organic-inorganic composite ultraviolet absorber. Firstly, a sol-gel method is used to prepare an inorganic ultraviolet absorber, rare earth cerate A2Ce2O7 (A=La, Gd or Y), which has a smaller bandgap, can absorb light of shorter wavelength and has excellent ultraviolet absorption performance; secondly, an organic amine hydrochloride is used to chemically modify a benzophenone compound, thereby increasing the stability of the benzophenone compound and its compatibility with a matrix resin; finally, the organic-inorganic composite ultraviolet absorber is prepared by self-assembly, and the rare earth cerate and the benzophenone hydrochloride produce a synergistic effect, so that the organic-inorganic composite ultraviolet absorber has excellent absorption performance in the ultraviolet region. When the organic-inorganic composite ultraviolet absorber is added to an organic resin, the ultraviolet aging resistance of the organic resin can be significantly improved, which plays a very important role in expanding the application field of the organic resin.
[0016] Specifically, in step a, the benzophenone compound is one or more of 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone or 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone. The organic amine hydrochloride is one or more of 2-chloroethylamine hydrochloride, 2-methylaminoethyl chloride hydrochloride or 3-dimethylaminopropyl chloride hydrochloride.
[0017] Furthermore, in step a, the molar ratio of the benzophenone compound to the organic amine hydrochloride is 1:1 to 1:2.
[0018] Furthermore, in step a, the acid binding agent is potassium carbonate.
[0019] Furthermore, in step a, the molar ratio of the benzophenone compound to the acid binding agent is 1:1 to 1:2.
[0020] Furthermore, in step a, the organic solvent is acetone.
[0021] Furthermore, in step a, the molar ratio of the benzophenone compound to acetone is 1:5 to 1:10.
[0022] Furthermore, in step a, the insulation reaction time is 4h to 5h.
[0023] Specifically, in step a, after the reaction is completed, ether is added to the reaction solution for extraction, the liquids are separated, the extract is retained, and the extract is dried by rotary evaporation to obtain benzophenone hydrochloride.
[0024] Furthermore, in step b, the molar ratio of the rare earth nitrate to cerium nitrate is 1:1 to 1:2.
[0025] Specifically, in step b, the rare earth nitrate includes lanthanum nitrate, gadolinium nitrate or yttrium nitrate.
[0026] Furthermore, in step b, the total concentration of metal ions in the mixed salt solution is 0.1 mol / L to 0.5 mol / L.
[0027] Furthermore, in step b, the complexing agent is one or more of citric acid, malic acid, malonic acid, succinic acid, succinic acid or glycolic acid.
[0028] Furthermore, in step b, the molar ratio of the complexing agent to the total amount of metal ions in the mixed salt solution is 1:1 to 1:2.
[0029] Furthermore, in step b, the stabilizer is one or more of ethylene glycol, ethylene glycol diglycidyl ether or propylene glycol.
[0030] Furthermore, in step b, the molar ratio of the stabilizer to the complexing agent is 1:1 to 1:2.
[0031] Furthermore, in step b, the calcination temperature is 400° C. to 600° C., and the calcination time is 2 h to 4 h.
[0032] Furthermore, in step c, the molar ratio of the silane coupling agent to the rare earth cerate is 1:50 to 1:100.
[0033] Specifically, in step c, the silane coupling agent is one or more of vinyl triethoxy silane, vinyl trimethoxy silane or vinyl tri (β-methoxyethoxy) silane.
[0034] Furthermore, in step c, the molar ratio of the rare earth cerate to the benzophenone hydrochloride is 1:2 to 1:3.
[0035] Furthermore, in step c, the concentration of the rare earth cerate in the rare earth cerate dispersion is 0.05 mol / L to 0.1 mol / L.
[0036] Furthermore, in step c, the stirring reaction time is 2h to 3h.
[0037] In a third aspect, the present invention also provides the use of an organic-inorganic composite ultraviolet absorber in the preparation of an ultraviolet aging-resistant polyethylene sheet.
[0038] In a fourth aspect, the present invention provides an anti-ultraviolet aging polyethylene sheet, comprising the organic-inorganic composite ultraviolet absorber.
[0039] The organic-inorganic composite ultraviolet absorber provided by the present invention is added to the polyethylene resin system, which can significantly improve the anti-ultraviolet aging performance of the polyethylene resin, so that it can be used for a long time in an outdoor strong ultraviolet radiation environment without performance degradation, thereby helping to increase the service life of the polyethylene sheet and reduce replacement and maintenance costs. At the same time, the above-mentioned organic-inorganic composite ultraviolet absorber is also beneficial to improving the mechanical properties of the polyethylene sheet, so that it can meet the use requirements of various application prospects.
[0040] Specifically, the anti-ultraviolet aging polyethylene sheet comprises the following raw material components in parts by weight: 100 parts of high-density polyethylene resin, 20 to 40 parts of linear low-density polyethylene resin, 5 to 10 parts of polyethylene elastomer, 5 to 10 parts of ethylene-vinyl acetate copolymer, 1 to 5 parts of organic-inorganic composite ultraviolet absorber and 1 to 2 parts of auxiliary agent;
[0041] Wherein, the auxiliary agent includes one or more of lubricants, antioxidants or colorants.
[0042] The anti-ultraviolet aging polyethylene sheet provided by the present invention selects high-density polyethylene resin as the base material, and is matched with linear low-density polyethylene resin, polyethylene elastomer and ethylene-vinyl acetate copolymer, so that the polyethylene sheet has excellent compressive strength, tensile strength and wear resistance, and effectively improves the safety of the polyethylene sheet when used in special environments. At the same time, the organic-inorganic composite ultraviolet absorber is added to significantly improve the ultraviolet absorption performance of the polyethylene sheet. At the same time, it is also beneficial to further improve the mechanical properties of the polyethylene sheet to a certain extent, so that the polyethylene sheet can be applied to extreme environments such as high altitudes and strong ultraviolet rays, thereby expanding the application field of the polyethylene sheet.
[0043] Furthermore, the density of the high-density polyethylene resin is 0.94 g / cm 3 ~0.96g / cm 3 , the melt flow rate at 230°C and 2.16kg is 0.4g / 10min~1.5g / 10min.
[0044] Furthermore, the density of the linear low-density polyethylene resin is 0.918 g / cm 3 ~0.935g / cm 3 , the melt flow rate at 230°C and 2.16kg is 2.5g / 10min~5.5g / 10min.
[0045] Furthermore, the content of α-octene in the polyethylene elastomer is 20 wt% to 30 wt%, and the melt flow rate at 230° C. and 2.16 kg is 1.0 / 10 min to 5.0 g / 10 min.
[0046] Furthermore, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 18 wt% to 28 wt%, and the melt flow rate at 230° C. and 2.16 kg is 2.0 / 10 min to 8.0 / 10 min.
[0047] The preferred resin matrix of the polyethylene sheet is beneficial to improving the mechanical properties of the polyethylene sheet and obtaining a polyethylene sheet with a balance of rigidity and toughness.
[0048] It should be noted that the lubricant, antioxidant or colorant described in the present invention can be selected from conventional lubricants, antioxidants or colorants in the art, and the present invention does not make any special limitation.
[0049] In a fifth aspect, the present invention provides a method for preparing a UV-resistant polyethylene sheet, comprising at least the following steps:
[0050] S1, weighing each component according to the designed ratio of the coating, and uniformly mixing the weighed high-density polyethylene resin, linear low-density polyethylene resin, polyethylene elastomer, ethylene-vinyl acetate copolymer, organic-inorganic composite ultraviolet absorber and additives to obtain a mixed material;
[0051] S2, melt-extrude the mixture through a twin-screw extruder to obtain an anti-ultraviolet aging polyethylene sheet.
[0052] The above preparation method is simple to operate, has no complicated procedures, does not require special equipment, is low in cost, and is suitable for industrial large-scale production. The prepared polyethylene sheet has excellent mechanical properties and anti-ultraviolet aging properties and has broad market prospects.
[0053] In a sixth aspect, the present invention provides the use of the above-mentioned anti-ultraviolet aging polyethylene sheet in railway height adjustment pads.
[0054] The organic-inorganic composite ultraviolet absorber provided by the present invention has good compatibility with the polyethylene resin system, can greatly improve the anti-ultraviolet aging performance of the polyethylene plate at a relatively low addition amount, and is also beneficial to improving the mechanical properties of the polyethylene plate, obtaining a polyethylene plate with a balance of rigidity and toughness, meeting the use requirements in various environments, and has a high application prospect in the field of railway height adjustment pads. The preparation method is simple, the cost is low, and the practical value is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is an infrared spectrum of 2-hydroxy-4-methoxybenzophenone hydrochloride prepared in Example 1 of the present invention;
[0056] Figure 2 This is a SEM image of La2Ce2O7 prepared in Example 1 of the present invention;
[0057] Figure 3 This is the XRD pattern of La2Ce2O7 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0059] Example 1
[0060] This embodiment provides an organic-inorganic composite ultraviolet diluent, and the preparation method includes the following steps:
[0061] Step a, 2-hydroxy-4-methoxybenzophenone and potassium carbonate are added to a three-necked flask in a molar ratio of 1:1, acetone is added to dissolve, the molar ratio of 2-hydroxy-4-methoxybenzophenone to acetone is 1:5, and then 3-dimethylaminopropyl chloride hydrochloride is added, the molar ratio of 2-hydroxy-4-methoxybenzophenone to 3-dimethylaminopropyl chloride hydrochloride is 1:1, heating and stirring, condensing and refluxing for 4h, adding ether for extraction, the molar ratio of ether to acetone is 1:1, standing for separation, and the extract is rotary evaporated to dryness to obtain 2-hydroxy-4-methoxybenzophenone hydrochloride, whose structural formula is shown below:
[0062]
[0063] Step b, dissolving lanthanum nitrate and cerium nitrate in distilled water at a molar ratio of 1:1 to prepare a mixed salt solution with a total metal ion concentration of 0.2 mol / L;
[0064] Add citric acid and ethylene glycol to the above mixed salt solution, the molar ratio of citric acid to the total amount of metal ions in the mixed salt solution is 1:1, and the molar ratio of ethylene glycol to citric acid is 1:1. Stir at room temperature for 2 hours, add ammonia water to adjust the pH of the solution to 6, place the above solution in a water bath heating pot, continue heating and stirring at 100°C until the sample is in a gel state, then transfer to a 70°C oven and dry for 12 hours, grind to a particle size not exceeding 100 mesh, and then place in a box-type resistance furnace and calcine at 500°C for 3 hours to obtain La2Ce2O7.
[0065] Step c, adding vinyl triethoxysilane and La2Ce2O7 in a molar ratio of 1:100 to water, stirring for 1 hour, and obtaining a La2Ce2O7 dispersion with a La2Ce2O7 concentration of 0.05 mol / L; adding the above-prepared 2-hydroxy-4-methoxybenzophenone hydrochloride to the La2Ce2O7 dispersion, the molar ratio of La2Ce2O7 to 2-hydroxy-4-methoxybenzophenone hydrochloride is 1:2, stirring at room temperature for 2 hours, filtering, and drying to obtain an organic-inorganic composite ultraviolet absorber.
[0066] The infrared spectrum of 2-hydroxy-4-methoxybenzophenone hydrochloride prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that 2-hydroxy-4-methoxybenzophenone and 3-dimethylaminopropyl chloride hydrochloride undergo a substitution reaction at 2925cm -1 and 2850cm -1 The characteristic peak of tertiary amine stretching vibration appears at 1070 cm -1 A weak CN stretching vibration peak appears at 1703 cm -1 The stretching vibration characteristic peak of keto group C=O and 1469cm -1 、1446cm-1 and 1343cm -1 The skeleton absorption peak of the benzene ring at 40° indicates that the 2-hydroxy-4-methoxybenzophenone hydrochloride shown in the above structure has been successfully prepared.
[0067] The SEM and XRD patterns of La2Ce2O7 prepared in this example are shown in Figure 2 , Figure 3 As shown, it can be proved that La2Ce2O7 with better crystal form was prepared in this example.
[0068] Example 2
[0069] This embodiment provides an organic-inorganic composite ultraviolet diluent, and the preparation method includes the following steps:
[0070] Step a, 2-hydroxy-4-n-octyloxybenzophenone and potassium carbonate are added to a three-necked flask in a molar ratio of 1:1.5, acetone is added to dissolve, the molar ratio of 2-hydroxy-4-n-octyloxybenzophenone to acetone is 1:10, and then 2-dimethylaminochloroethane hydrochloride is added, the molar ratio of 2-hydroxy-4-n-octyloxybenzophenone to 2-dimethylaminochloroethane hydrochloride is 1:1.5, heating and stirring, condensing and refluxing for 4.5h, adding ether for extraction, the molar ratio of ether to acetone is 1:2, standing for separation, and the extract is rotary evaporated to dryness to obtain 2-hydroxy-4-n-octyloxybenzophenone hydrochloride, whose structural formula is shown below:
[0071]
[0072] Step b, dissolving gadolinium nitrate and cerium nitrate in distilled water at a molar ratio of 1:2 to prepare a mixed salt solution with a total metal ion concentration of 0.1 mol / L;
[0073] Malic acid and propylene glycol were added to the above mixed salt solution, the molar ratio of citric acid to the total amount of metal ions in the mixed salt solution was 1:2, and the molar ratio of propylene glycol to malic acid was 1:2. The solution was stirred at room temperature for 2 hours, and ammonia water was added to adjust the pH of the solution to 6.8. The above solution was placed in a water bath heating pot, and heated and stirred continuously at 90°C until the sample was in a gel state. Then, it was transferred to a 65°C oven and dried for 15 hours. The sample was ground to a particle size not exceeding 100 mesh, and then placed in a box-type resistance furnace and calcined at 400°C for 4 hours to obtain Ga2Ce2O7.
[0074] Step c, adding vinyl triethoxysilane and Ga2Ce2O7 to water in a molar ratio of 1:80, stirring for 1 hour, and obtaining a Ga2Ce2O7 dispersion with a Ga2Ce2O7 concentration of 0.08 mol / L; adding the above-prepared 2-hydroxy-4-methoxybenzophenone hydrochloride to the Ga2Ce2O7 dispersion, the molar ratio of Ga2Ce2O7 to 2-hydroxy-4-octyloxybenzophenone hydrochloride is 1:3, stirring at room temperature for 2 hours, filtering, and drying to obtain an organic-inorganic composite ultraviolet absorber.
[0075] Example 3
[0076] This embodiment provides an organic-inorganic composite ultraviolet diluent, and the preparation method includes the following steps:
[0077] Step a, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone and potassium carbonate are added to a three-necked flask in a molar ratio of 1:2, acetone is added to dissolve, the molar ratio of 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone to acetone is 1:8, and then 2-chloroethylamine hydrochloride is added, the molar ratio of 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone to 2-chloroethylamine hydrochloride is 1:2, heating and stirring, condensing and refluxing for 5h, adding ether for extraction, the molar ratio of ether to acetone is 1:1.5, standing for separation, and the extract is rotary evaporated to dryness to obtain 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone hydrochloride, whose structural formula is shown below:
[0078]
[0079] Step b, dissolving yttrium nitrate and cerium nitrate in distilled water at a molar ratio of 1:1.5 to prepare a mixed salt solution with a total metal ion concentration of 0.5 mol / L;
[0080] Add succinic acid and ethylene glycol diglycidyl ether to the above mixed salt solution, the molar ratio of citric acid to the total amount of metal ions in the mixed salt solution is 1:1.5, and the molar ratio of ethylene glycol diglycidyl ether to succinic acid is 1:1.5. Stir at room temperature for 1 hour, add ammonia water to adjust the pH of the solution to 6.5, place the above solution in a water bath heating pot, continue heating and stirring at 95°C until the sample is in a gel state, then transfer it to a 60°C oven and dry it for 18 hours, grind it to a particle size not exceeding 100 mesh, and then put it into a box-type resistance furnace and calcine it at 600°C for 2 hours to obtain Y2Ce2O7.
[0081] Step c, adding vinyl triethoxysilane and Y2Ce2O7 to water in a molar ratio of 1:50, stirring for 1 hour, and obtaining a Y2Ce2O7 dispersion with a Y2Ce2O7 concentration of 0.1 mol / L; adding the above-prepared 2-hydroxy-4-methoxybenzophenone hydrochloride to the Y2Ce2O7 dispersion, the molar ratio of Y2Ce2O7 to 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone hydrochloride is 1:2.5, stirring at room temperature for 2 hours, filtering, and drying to obtain an organic-inorganic composite ultraviolet absorber.
[0082] Example 4
[0083] This embodiment provides an anti-ultraviolet aging polyethylene sheet, comprising the following components in parts by weight:
[0084] 100 parts of high-density polyethylene (HDPE) resin, 30 parts of linear low-density polyethylene (LLDPE) resin, 5 parts of polyethylene elastomer (POE), 5 parts of ethylene-vinyl acetate copolymer (EVA), 2 parts of the organic-inorganic composite ultraviolet absorber prepared in Example 1 and 1 part of an auxiliary agent;
[0085] The auxiliary agent includes a lubricant, an antioxidant and a colorant in a mass ratio of 1:1:2, wherein the lubricant is zinc stearate, the antioxidant is antioxidant 1076, and the colorant is black masterbatch.
[0086] The HDPE resin density is 0.95 g / cm 3 The melt flow rate at 230°C and 2.16 kg is 1.0 g / 10 min; the LLDPE resin density is 0.92 g / cm 3 , the melt flow rate at 230°C and 2.16kg is 5g / 10min; the α-octene content in the POE resin is 25wt%, and the melt flow rate at 230°C and 2.16kg is 3g / 10min; the vinyl acetate content in the EVA resin is 28wt%, and the melt flow rate at 230°C and 2.16kg is 15g / 10min.
[0087] The method for preparing the above-mentioned anti-ultraviolet aging polyethylene sheet comprises the following steps:
[0088] S1, weighing each component according to the weight of the formula, mixing the weighed LLDPE resin, POE resin, EVA resin, the organic-inorganic composite ultraviolet absorber prepared in Example 1 and the additives at a rate of 600 r / min for 10 min to obtain a mixed material;
[0089] S2, melt-extrude the above mixed material at 220° C. through a twin-screw extruder, pull and cut to obtain an anti-ultraviolet aging polyethylene sheet.
[0090] Example 5
[0091] This embodiment provides an anti-ultraviolet aging polyethylene sheet, comprising the following components in parts by weight:
[0092] 100 parts of high-density polyethylene (HDPE) resin, 20 parts of linear low-density polyethylene (LLDPE) resin, 10 parts of polyethylene elastomer (POE), 8 parts of ethylene-vinyl acetate copolymer (EVA), 1 part of the organic-inorganic composite ultraviolet absorber prepared in Example 2, and 2 parts of auxiliary agents;
[0093] The auxiliary agent includes a lubricant, an antioxidant and a colorant in a mass ratio of 1:1:2, wherein the lubricant is zinc stearate, the antioxidant is antioxidant 1076, and the colorant is black masterbatch.
[0094] The HDPE resin density is 0.95 g / cm 3 The melt flow rate at 230°C and 2.16 kg is 1.0 g / 10 min; the LLDPE resin density is 0.92 g / cm 3 , the melt flow rate at 230°C and 2.16kg is 5g / 10min; the α-octene content in the POE resin is 25wt%, and the melt flow rate at 230°C and 2.16kg is 3g / 10min; the vinyl acetate content in the EVA resin is 28wt%, and the melt flow rate at 230°C and 2.16kg is 15g / 10min.
[0095] The method for preparing the above-mentioned anti-ultraviolet aging polyethylene sheet comprises the following steps:
[0096] S1, weighing each component according to the weight of the formula, mixing the weighed LLDPE resin, POE resin, EVA resin, the organic-inorganic composite ultraviolet absorber prepared in Example 2 and the additives at a rate of 600 r / min for 20 min to obtain a mixed material;
[0097] S2, melt-extrude the above mixed material at 210° C. through a twin-screw extruder, pull and cut to obtain an anti-ultraviolet aging polyethylene sheet.
[0098] Example 6
[0099] This embodiment provides an anti-ultraviolet aging polyethylene sheet, comprising the following components in parts by weight:
[0100] 100 parts of high-density polyethylene (HDPE) resin, 40 parts of linear low-density polyethylene (LLDPE) resin, 8 parts of polyethylene elastomer (POE), 10 parts of ethylene-vinyl acetate copolymer (EVA), 5 parts of the organic-inorganic composite ultraviolet absorber prepared in Example 3 and 1 part of an auxiliary agent;
[0101] The auxiliary agent includes a lubricant, an antioxidant and a colorant in a mass ratio of 1:1:2, wherein the lubricant is zinc stearate, the antioxidant is antioxidant 1076, and the colorant is black masterbatch.
[0102] The HDPE resin density is 0.95 g / cm 3 The melt flow rate at 230°C and 2.16 kg is 1.0 g / 10 min; the LLDPE resin density is 0.92 g / cm 3 , the melt flow rate at 230°C and 2.16kg is 5g / 10min; the α-octene content in the POE resin is 25wt%, and the melt flow rate at 230°C and 2.16kg is 3g / 10min; the vinyl acetate content in the EVA resin is 28wt%, and the melt flow rate at 230°C and 2.16kg is 15g / 10min.
[0103] The method for preparing the above-mentioned anti-ultraviolet aging polyethylene sheet comprises the following steps:
[0104] S1, weighing each component according to the weight of the formula, mixing the weighed LLDPE resin, POE resin, EVA resin, the organic-inorganic composite ultraviolet absorber prepared in Example 3 and the additives at a rate of 600 r / min for 15 min to obtain a mixed material;
[0105] S2, melt-extrude the above mixed material at 230° C. through a twin-screw extruder, pull and cut to obtain an anti-ultraviolet aging polyethylene sheet.
[0106] Comparative Example 1
[0107] This comparative example provides a polyethylene plate, which is different from Example 4 only in that the organic-inorganic composite ultraviolet absorber prepared in Example 1 is not added, and the rest is exactly the same, which will not be repeated here.
[0108] Comparative Example 2
[0109] This comparative example provides a polyethylene plate, which is different from Example 4 only in that the organic-inorganic composite ultraviolet absorber is replaced by an equal amount of 2-hydroxy-4-methoxybenzophenone. The rest is exactly the same and will not be repeated here.
[0110] Comparative Example 3
[0111] This comparative example provides a polyethylene plate, which is different from Example 4 only in that the organic-inorganic composite ultraviolet absorber is replaced by an equal amount of La2Ce2O7. The rest is exactly the same and will not be repeated here.
[0112] Comparative Example 4
[0113] This comparative example provides a polyethylene plate, which is different from Example 4 only in that the organic-inorganic composite UV absorber is replaced by an equal amount of polyvinylsiloxane-modified 2-hydroxy-4-methoxybenzophenone, and the rest is exactly the same and will not be repeated here.
[0114] The preparation method of polyvinylsiloxane modified 2-hydroxy-4-methoxybenzophenone is:
[0115] Weigh 1.14 g of 2-hydroxy-4-methoxybenzophenone into a three-necked flask, add 0.71 g of glycidyl methacrylate and 5 mL of chloroform, shake well, add 0.50 g of Amberlyst-15 ion exchange resin after it is fully dissolved, then put the three-necked flask into an ultrasonic water bath, heat to 60 ° C and react for 3 hours, filter to remove the ion exchange resin, and use a rotary evaporator to evaporate the solvent from the filtrate to obtain an intermediate.
[0116] 0.40 g of the intermediate and 0.40 g of vinyl silicone oil were weighed and added to a dropping funnel, and 10 mL of a mixed solvent of toluene and anhydrous ethanol (volume ratio 1:1) was measured and added thereto (as component A).
[0117] Weigh 2 mg of azobisisobutyronitrile, dissolve it in 10 mL of a mixed solvent of toluene and anhydrous ethanol (volume ratio 1:1), and add it to another dropping funnel (as component B).
[0118] Weigh 0.10g of the intermediate and 0.10g of vinyl silicone oil into a three-necked flask, add 3mg of azobisisobutyronitrile and 30mL of a mixed solvent of toluene and anhydrous ethanol (volume ratio of 1:1), stir and heat to react for 10min, then add component A and component B dropwise at the same time, control the dropwise addition within 3h, keep warm for 2h, and use a rotary evaporator to evaporate the solvent to finally obtain polyvinylsiloxane-modified 2-hydroxy-4-methoxybenzophenone.
[0119] Comparative Example 5
[0120] This comparative example provides a polyethylene plate, which is different from Example 4 only in that La2Ce2O7 in the preparation process of the organic-inorganic composite ultraviolet absorber is replaced by an equal amount of TiO2, and the rest is exactly the same and will not be repeated here.
[0121] The polyethylene sheets in the above examples and comparative examples were subjected to the following performance tests, wherein the tensile properties and elongation at break were tested in accordance with the standard GB / T1040.2-2022. The UV aging test was conducted in accordance with GB / T14522-2008, and the samples were irradiated by UVA-340 with an irradiance of 0.89 W / m 2 , exposure cycle (70℃ UV light 8h, 50℃ condensation 4h), UV accelerated aging test was carried out for 500h and then tested. The results are shown in Table 1.
[0122] Table 1 Performance comparison of polyethylene board before and after UV irradiation
[0123]
[0124]
[0125] From the test results of each embodiment and comparative example in Table 1, it can be seen that the addition of organic-inorganic composite ultraviolet absorber can significantly improve the anti-ultraviolet performance and mechanical strength of polyethylene sheet. From the data of Example 4 and Comparative Examples 1 to 3, it can be seen that the addition effect of organic-inorganic composite ultraviolet absorber compound is better than that of no ultraviolet absorber and single ultraviolet absorber. From the data of Example 4 and Comparative Examples 4 to 5, it can be seen that the anti-ultraviolet effect of 2-hydroxy-4-methoxybenzophenone modified by 3-dimethylaminopropyl chloride hydrochloride is better than that of ultraviolet absorbers modified by other methods.
[0126] Other organic-inorganic composite ultraviolet absorbers prepared by using the benzophenone compounds defined in the present invention and organic amine hydrochlorides can achieve the same technical effects as those of Examples 1 to 3.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An organic-inorganic composite ultraviolet absorber, characterized in that: Including benzophenone hydrochloride and rare earth cerate A2Ce2O7 shown in formula (Ⅰ); Among them, R1 and R2 are H or CH3, R3 is a C2-C3 alkyl group, R4 is a C1-C8 alkyl group, R5 is H or a sulfonic acid group; and A represents La, Gd or Y.
2. The method for preparing the organic-inorganic composite ultraviolet absorber according to claim 1, characterized in that: The steps include: Step a, adding a benzophenone compound represented by formula (II), an organic amine hydrochloride represented by formula (III) and an acid binding agent into an organic solvent, heating to reflux, and keeping the temperature to react to obtain a benzophenone hydrochloride represented by formula (I); Step b, dissolving rare earth nitrate and cerium nitrate in water to obtain a mixed salt solution; adding a complexing agent and a stabilizer to the mixed salt solution, mixing evenly, adjusting the pH to 6-7, heating at 90° C.-100° C. to a gel state, drying, grinding, and calcining to obtain rare earth cerate; Step c, adding the rare earth cerate and the silane coupling agent into water, mixing evenly, to obtain a rare earth cerate dispersion; adding the benzophenone hydrochloride into the rare earth cerate dispersion, stirring for reaction, solid-liquid separation, and drying to obtain an organic-inorganic composite ultraviolet absorber.
3. The method for preparing the organic-inorganic composite ultraviolet absorber according to claim 2, characterized in that: In step a, the molar ratio of the benzophenone compound to the organic amine hydrochloride is 1:1 to 1:2; and / or In step a, the acid binding agent is potassium carbonate; and / or In step a, the organic solvent is acetone; and / or In step a, the insulation reaction time is 4h to 5h.
4. The method for preparing the organic-inorganic composite ultraviolet absorber according to claim 2, characterized in that: In step b, the molar ratio of the rare earth nitrate to cerium nitrate is 1:1 to 1:2; and / or In step b, the complexing agent is one or more of citric acid, malic acid, malonic acid, succinic acid, succinic acid or glycolic acid; and / or In step b, the molar ratio of the complexing agent to the total amount of metal ions in the mixed salt solution is 1:1 to 1:2; and / or In step b, the stabilizer is one or more of ethylene glycol, ethylene glycol diglycidyl ether or propylene glycol; and / or In step b, the molar ratio of the stabilizer to the complexing agent is 1:1 to 1:2; and / or In step b, the calcination temperature is 400° C. to 600° C., and the calcination time is 2 h to 4 h; and / or In step c, the molar ratio of the silane coupling agent to the rare earth cerate is 1:50 to 1:100; and / or In step c, the molar ratio of the rare earth cerate to the benzophenone hydrochloride is 1:2 to 1:3; and / or In step c, the stirring reaction time is 2h to 3h.
5. Use of the organic-inorganic composite ultraviolet absorber according to claim 1 in the preparation of ultraviolet aging resistant polyethylene sheets.
6. A UV-resistant polyethylene sheet, characterized in that: It includes the organic-inorganic composite ultraviolet absorber as described in claim 1.
7. The anti-ultraviolet aging polyethylene sheet according to claim 6, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of high-density polyethylene resin, 20 to 40 parts of linear low-density polyethylene resin, 5 to 10 parts of polyethylene elastomer, 5 to 10 parts of ethylene-vinyl acetate copolymer, 1 to 5 parts of organic-inorganic composite ultraviolet absorber and 1 to 2 parts of auxiliary agent; Wherein, the auxiliary agent includes one or more of lubricants, antioxidants or colorants.
8. The anti-ultraviolet aging polyethylene sheet according to claim 7, characterized in that: The density of the high-density polyethylene resin is 0.94 g / cm 3 ~0.96g / cm 3 , a melt flow rate of 0.4 g / 10 min to 1.5 g / 10 min at 230° C. and 2.16 kg; and / or The density of the linear low-density polyethylene resin is 0.918 g / cm 3 ~0.935g / cm 3 , a melt flow rate of 2.5 g / 10 min to 5.5 g / 10 min at 230° C. and 2.16 kg; and / or The polyethylene elastomer has an α-octene content of 20 wt% to 30 wt%, and a melt flow rate of 1.0 / 10min to 5.0 g / 10min at 230° C. and 2.16 kg; and / or The vinyl acetate content of the ethylene-vinyl acetate copolymer is 18wt% to 28wt%, and the melt flow rate at 230°C and 2.16kg is 2.0 / 10min to 8.0 / 10min.
9. The method for preparing the UV-resistant polyethylene sheet according to claim 7 or 8, characterized in that: At least the following steps are included: S1, weighing each component according to the designed ratio of the coating, and uniformly mixing the weighed high-density polyethylene resin, linear low-density polyethylene resin, polyethylene elastomer, ethylene-vinyl acetate copolymer, organic-inorganic composite ultraviolet absorber and additives to obtain a mixed material; S2, melt-extrude the mixture through a twin-screw extruder to obtain an anti-ultraviolet aging polyethylene sheet.
10. Use of the anti-ultraviolet aging polyethylene sheet according to any one of claims 6 to 8 in railway height adjustment pads.